Praktik Penanganan Ekstremitas Bawah di Fasilitas Kesehatan Tingkat Pertama Puskesmas Koeloda - Kanisius Emanuel Kaki; Ermelinda Rosena Ongge; Sofia Uge Nau; Robertus Lili Bile (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Lower extremity injuries are one of the health problems that are often encountered in first-level health care facilities, especially due to physical activity, sports, and accidents. This study aims to describe the practice of handling lower extremity injuries at the Koiloda Health Center. The research method uses a qualitative descriptive approach through direct observation and interviews with health workers. The results showed that the most commonly treated types of injuries included muscle strains, ankle ligament sprains, contusions, open wounds, and suspected fractures. Treatment is carried out according to the standards of first-level health services, namely through initial examinations, the application of RICE principles (Rest, Ice, Compression, Elevation), simple immobilization, pain management, wound care, and referral to advanced health facilities in severe cases. Although the handling practice has been carried out according to procedures, this study also found that there are limitations in facilities and supporting facilities that can affect the quality of service. The conclusion of the study emphasizes that the Koeloda Health Center has carried out the handling of lower extremity injuries according to standards, but it is necessary to improve facilities, training health workers, and support for the referral system so that services are more optimal and comprehensive.